The Power of One or Power in Numbers?: Analyzing the Effect of Minority Leaders on Diversity Policy and Practice. (May 2015) - Cook, Alison; Glass, Christy
This study analyzes the impact of racial/ethnic minority leaders on equity and diversity policies. Previous research finds that minority leaders are associated with reduced inequality, yet the ways in which these leaders impact organizational policies are understudied. Our analysis relies on a unique dataset of corporate practices, CEO race/ethnicity, and board member race/ethnicity in Fortune 500 firms from 2001 to 2010. The authors find that while minority CEOs have minimal impact on equity policies, diverse boards are significantly associated with equitable practices. They conclude that board diversity is critical for shaping corporate practice related to equity and diversity.